1977
DOI: 10.1002/ijc.2910200403
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Epstein‐Barr virus and undifferentiated nasopharyngeal carcinoma: Correlated nucleic acid hybridization and histopathological examination

Abstract: In order to examine critically the closeness of association between Epstein-Barr virus (EBV) DNA and nasopharyngeal carcinoma (NPC) a correlated histopathological and nucleic acid hybridization study was performed on 51 undifferentiated NPC, 4 NPC with some signs of squamous differentiation, 7 nasophayngeal tumors of other histological types and 14 head and neck carcinomas located outside the nasopharynx. All 51 undifferentiated NPCs contained significant numbers of EBV-genome copies per cell. Two of the somew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(60 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…EBV-positive/MSI NPCs have been reported in patients collected from the Unites States (2/9, 22%) [22] and by Trimeche et al [20] in patients from Tunisia (8/49, 16%). Current literature suggests that EBV infection is an early event in the pathogenesis of EBV-positive NPCs [2,32,33]. An in vitro study with NPC and other epithelial cell lines showed that EBV DNase BGLF5 can induce DNA strand breaks and decrease expression of MMR proteins leading to MSI [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBV-positive/MSI NPCs have been reported in patients collected from the Unites States (2/9, 22%) [22] and by Trimeche et al [20] in patients from Tunisia (8/49, 16%). Current literature suggests that EBV infection is an early event in the pathogenesis of EBV-positive NPCs [2,32,33]. An in vitro study with NPC and other epithelial cell lines showed that EBV DNase BGLF5 can induce DNA strand breaks and decrease expression of MMR proteins leading to MSI [34].…”
Section: Discussionmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) has been implicated in the pathogenesis of most NPCs [2]. Although the 5-year survival rate in early stage disease is over 80% with chemoradiation, the 5-year survival rate in stage IV disease is less than 10% [3], suggesting a need for better treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…IgA antibodies to these 2 antigens were also often demonstrable in sera from NPC patients (Henle & Henle, 1976;Henle et al, 1977). This pattern of elevated IgG and IgA antibodies to VCA and EA (D) has been found uniformly in NPC patients, whether from low-or high-risk areas (Henle & Henle, 1976;Henle et al, 1977;de The et al, 1978;Klein, 1979;Lanier et al, 1981). The association of NPC with EBV has been further strengthened by the detection of EBV genomes in the malignant epithelial cells by nucleicacid hybridization techniques (zur Hausen et al, 1970(zur Hausen et al, , 1974Nonoyama et al, 1973;Wolf et al, 1973Wolf et al, , 1975 and by demonstration of EBV nuclear antigen (EBNA) in the carcinoma cells (Huang et al, 1974;Klein et al, 1974).…”
Section: The Epstein-barr Virus (Ebv) Was Originally Detected In Cultmentioning
confidence: 99%
“…Two years later tests for EBV-specific precipitating antibodies suggested an association of the virus with nasopharyngeal carcinoma (NPC) in East African and American patients (Old et al, 1966). It was rapidly shown thereafter that NPC patients had elevated titres of IgG antibodies to EBV viral capsid antigen (VCA) and to the diffuse (D) component of the early-antigen (EA) complex (Henle et al, 1970(Henle et al, , 1971(Henle et al, , 1977. IgA antibodies to these 2 antigens were also often demonstrable in sera from NPC patients (Henle & Henle, 1976;Henle et al, 1977).…”
Section: The Epstein-barr Virus (Ebv) Was Originally Detected In Cultmentioning
confidence: 99%
See 1 more Smart Citation